Plasma lipids, amino acids, and their metabolic pathways as potential biomarkers for differential diagnosis of cold and heat syndrome asthma in children: a preliminary study - Yi Sun; Yi Sun; Lianzhan Huang; Wenhui Yao; Zhengguang Chen; Dong Cui; Xuansheng Ding; Lisheng Wan (Frontiers in Pediatrics, 2025)
BackgroundChildhood asthma has a significant effect on growth and development. Traditional Chinese Medicine (TCM) has notable advantages in asthma treatment; however, a modern scientific basis for the differentiation of cold and heat syndromes in asthma remains lacking.MethodsThis study employed non-targeted metabolomics to analyze the plasma metabolic profiles in children aged 5–14 years with cold or heat syndrome asthma. Plasma metabolites were examined to identify and compare metabolic differences among children with asthma and healthy controls, as well as between cold and heat asthma syndromes, with the aim of uncovering potential biomarkers and providing a foundation for differential diagnosis.ResultsOf the 92 participants, 48 had cold syndrome asthma, 14 had heat syndrome asthma, and 30 were healthy controls. A total of 50 differential plasma metabolites were identified between the TCM asthma syndrome groups and healthy controls in both positive and negative ion modes. These metabolites were primarily phospholipids and amino acids enriched in the lipid metabolism, amino acid metabolism, and glucose metabolism pathways. Furthermore, 18 differential metabolites were identified between the cold and heat asthma groups, with significant enrichment in the amino acid metabolic pathways. Notably, 36 common differential metabolites that mainly were lipids, amino acids and its related metabolites between cold asthma and heat asthma, cold asthma and the healthy group, and heat asthma and the healthy group were identified of which can be considered as biomarkers.ConclusionsLipids, amino acids, and their associated metabolic pathways have been identified as potential biomarkers for distinguishing cold and heat asthma syndromes in children. These findings contribute to the modern interpretation of TCM syndrome differentiation and may support the evaluation of the therapeutic effects of TCM-based asthma treatment.